Role of specialized nutrition for wound healing: a narrative review - Cianciulli, Angelo; Delli Poggi, Alessandro; Giannetta, Noemi; Fiorinelli, Massimo; Taraborelli, Emanuela; Roncone, Antonella; Biasiucci, Raissa; Figura, Mariachiara; Di Simone, Emanuele; Di Muzio, Marco (Progress in Nutrition, 2019)
Background. Wound healing is a dynamic process that depends not only on the interaction between different cellular factors involved in the tissue repair process but can also be adjuvant by a daily nutritional support. Therefore it can be considered a kind of specialized nutrition of which several elements favour the repair and wound healing process. Objective: The aim of this study was to verify the effect of beta-hydroxy-beta-methylbutyrate (HMB). To investigate the effects of the combination of arginine, beta-hydroxy-beta-methylbutyrate and glutamine in order to favour collagen deposition on the wound bed. Materials and Methods: The research was conducted by analysing publications of recent years and also by setting “title and abstract” as a search criterion. Results: From the studies conducted, it was shown that by analysing the combined action of the amino acid mixture in relation to collagen deposition in humans, in just two weeks the integration with arginine, HMB and glutamine produced a significant increase in plasma levels of arginine and ornithine equal to 67%. Conclusions: HMB increases lean mass, improves muscle strength and exerts anti-catabolism. Glutamine is essential in the metabolism of lymphocytes, enterocytes and other cells with a rapid turnover. Collagen synthesis and scar formation are necessary for complete resolution of a wound.